Design, Synthesis and Biological Evaluation of Novel MDH Inhibitors Targeting Tumor Microenvironment - Sreenivasulu Godesi; Jeong-Ran Han; Jang-Keun Kim; Dong-Ik Kwak; Joohan Lee; Hossam Nada; Minkyoung Kim; Hyun-A Yang; Joo-Young Im; Hyun Seung Ban; Chang Hoon Lee; Yongseok Choi; et al. (MDPI AG, 2023)
MDH1 and MDH2 enzymes play an important role in the survival of lung cancer. In this study, a novel series of dual MDH1/2 inhibitors for lung cancer was rationally designed and synthesized, and their SAR was carefully investigated. Among the tested compounds, compound 50 containing a piperidine ring displayed an improved growth inhibition of A549 and H460 lung cancer cell lines compared with LW1497. Compound 50 reduced the total ATP content in A549 cells in a dose-dependent manner; it also significantly suppressed the accumulation of hypoxia-inducible factor 1-alpha (HIF-1α) and the expression of HIF-1α target genes such as GLUT1 and pyruvate dehydrogenase kinase 1 (PDK1) in a dose-dependent manner. Furthermore, compound 50 inhibited HIF-1α-regulated CD73 expression under hypoxia in A549 lung cancer cells. Collectively, these results indicate that compound 50 may pave the way for the development of next-generation dual MDH1/2 inhibitors to target lung cancer.